2009
DOI: 10.1007/s11105-009-0142-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Flooding-Response Genes in Eggplant Roots by Suppression Subtractive Hybridization

Abstract: Roots of eggplant (Solanum melongena L.) cv. Pingtong Long Eggplant (EG117) were subjected to ten flooding treatments. Messenger RNAs from plants subjected to flooding periods for 0.25 to 1 and 3 to 12 h as well as unflooded plants (control) were used as the tester and driver samples, respectively. Following suppression subtractive hybridization, polymerase chain reaction (PCR) products were ligated into a cloned vector for Escherichia coli-competent cell transformation, followed by nested PCR screening of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Plants were watered three times a week and fertilizer (17:36:39, N:P:K) applied once a week to maintain optimal growth for 30 days before the imposition of stress treatments. Pots containing 'H41' and 'H69' plants were subjected to four treatments: non-flooding at 20 • C (NFC, as control), flooding at 20 • C (FC, control temperature), non-flooding at 40 • C (NFH, high temperature), and flooding at 40 • C (FH), for periods of 0, 6, 12, 24, 48, 72, and 96 h in four growth chambers having a 14 h photoperiod at 300 mol m −2 s −1 radiation and 80% RH (Lin et al, 2010). In the case of flooding treatments, pots were randomly placed in 28 cm × 14 cm × 14 cm plastic buckets and subjected to flooding by filling the buckets with tap water to 5 cm above the soil surface.…”
Section: Plant Materials Culturing and Heat-and Flood-stress Treatmmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants were watered three times a week and fertilizer (17:36:39, N:P:K) applied once a week to maintain optimal growth for 30 days before the imposition of stress treatments. Pots containing 'H41' and 'H69' plants were subjected to four treatments: non-flooding at 20 • C (NFC, as control), flooding at 20 • C (FC, control temperature), non-flooding at 40 • C (NFH, high temperature), and flooding at 40 • C (FH), for periods of 0, 6, 12, 24, 48, 72, and 96 h in four growth chambers having a 14 h photoperiod at 300 mol m −2 s −1 radiation and 80% RH (Lin et al, 2010). In the case of flooding treatments, pots were randomly placed in 28 cm × 14 cm × 14 cm plastic buckets and subjected to flooding by filling the buckets with tap water to 5 cm above the soil surface.…”
Section: Plant Materials Culturing and Heat-and Flood-stress Treatmmentioning
confidence: 99%
“…However, heat-tolerant cultivars are able to form heads at mean temperatures higher than 25 • C. To expand the area of food production, crops are grown under stressful environments that likely lead to lower yields. The main contributing factors in the reduction of yield and quality in these areas are variations in climatic conditions such as flooding caused by rains (Lin et al, 2010). Heavy rainstorms and standing water can leave soils saturated for days before draining, making waterlogging a problem in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous studies showed that 75% of the 434 metabolites were increased when Arabidopsis plants were under cold stress (Cook et al 2004). Previous study also indicated that a larger number of genes involved in metabolic pathway were increased when plants were under stress conditions Zhang et al 2009;Lin et al 2010;Prabu et al 2011). It has been suggested that the AOX pathway can maintain the activity of TCA cycle enzymes to satisfy the plant's need for increased carbon skeletons (Padmasree and Raghavendra 1999;Raghavendra and Padmasree 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It uses common molecular biological techniques that do not require specialized equipment or analyses (Moody 2001). This method was very useful in screening new genes and construction of cDNA library (Lin et al 2010; Wang et al 2011; Dipnarayan et al 2011; Zhang et al 2011a, b; Zhou et al 2011; Prabu et al 2011; Yang et al 2011). Given the current understanding of ramie at the molecular level, this technique is a suitable method for the detection of low-abundance, differentially expressed transcripts that can lead to the isolation of putative disease resistance and defense-related genes.…”
Section: Introductionmentioning
confidence: 99%